2016
DOI: 10.14740/wjon966w
|View full text |Cite
|
Sign up to set email alerts
|

Myiasis on a Giant Squamous Cell Carcinoma of the Scalp: A Case Report and Review of Relevant Literature

Abstract: Non-melanoma skin cancer is the most common malignancy amongst Caucasians worldwide with basal cell and squamous cell cancer being the most common. Giant skin cancers are a relatively rare type of skin cancer that are, by definition, greater than 5 cm. This subtype by itself is associated with a significantly increased risk of complications and mortality. Myiasis is defined as infestation of body tissues of humans by dipterous larvae. Myiasis is often associated with malignant skin conditions. We describe a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…4 Another report described a rare case of cutaneous myiasis located on a giant squamous cell carcinoma of the scalp in a 95 year old female who underwent radiation of 5,000-6,000 cGy in 24 daily fractions, without reporting of outcomes. 33 To our knowledge, this retrospective study is the first to analyze the outcomes of giant NMSCs not amenable to surgery in a substantial group of older frail patients treated with definitive 3D CRT, demonstrating its feasibility and effectiveness in both curative and palliative settings.…”
Section: Discussionmentioning
confidence: 86%
“…4 Another report described a rare case of cutaneous myiasis located on a giant squamous cell carcinoma of the scalp in a 95 year old female who underwent radiation of 5,000-6,000 cGy in 24 daily fractions, without reporting of outcomes. 33 To our knowledge, this retrospective study is the first to analyze the outcomes of giant NMSCs not amenable to surgery in a substantial group of older frail patients treated with definitive 3D CRT, demonstrating its feasibility and effectiveness in both curative and palliative settings.…”
Section: Discussionmentioning
confidence: 86%
“…1). 5–7,17–104 A case series of Sowani et␣al 98 . with 83 patients was excluded from our study due to severe limitations in the eligibility methods, lack of precision in the clinical findings, and lack of histopathological confirmation.…”
Section: Resultsmentioning
confidence: 99%
“…The species classification can also vary according to its biological feeding behavior. The reader must be careful with the biological behavior of the larvae in tumor wounds 1–11,13–114 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that symptomatic improvement occurs immediately with the removal of the larvae. [ 28 ] Ivermectin given orally in just one dose of 150–200 mcg/kg body weight and repeated after 24 h has been reported to be effective in severe cases. [ 29 ] Shinohara et al .…”
Section: Discussionmentioning
confidence: 99%